2013
DOI: 10.1175/jtech-d-12-00174.1
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and Accuracy of an Airborne Scanning Laser System for Beach Surveys

Abstract: Airborne scanning laser technology provides an effective method to systematically survey surface topography and changes in that topography with time. In this paper, the authors describe the capability of a rapid-response lidar system in which airborne observations are utilized to describe results from a set of surveys of Narrabeen–Collaroy Beach, Sydney, New South Wales, Australia, over a short period of time during which significant erosion and deposition of the subaerial beach occurred. The airborne lidar da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Aerial methods are a popular alternative to on-ground methods as they can rapidly cover large areas at adequate resolution (e.g., Stockdon et al, 2002). In a limited number of studies, airborne laser scanning has been carried out before and after a storm event to measure beach change (Middleton et al, 2013;Sallenger et al, 2003), although the frequency of repeat deployments is limited by high costs. Annual surveys have been adopted in broad scale multidecadal programs, where measurement frequency is reduced to achieve broader spatial extent (e.g., Mason et al, 2000;Wijnberg and Terwindt, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Aerial methods are a popular alternative to on-ground methods as they can rapidly cover large areas at adequate resolution (e.g., Stockdon et al, 2002). In a limited number of studies, airborne laser scanning has been carried out before and after a storm event to measure beach change (Middleton et al, 2013;Sallenger et al, 2003), although the frequency of repeat deployments is limited by high costs. Annual surveys have been adopted in broad scale multidecadal programs, where measurement frequency is reduced to achieve broader spatial extent (e.g., Mason et al, 2000;Wijnberg and Terwindt, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Conveniently, the aircraft is permanently based at an airfield located 10 min flight time from Narrabeen, further facilitating very rapid deployment. Comparisons detailed in Middleton et al [101] of in-situ ATV RTK-GPS surveys from Narrabeen showed the airborne lidar data had a mean vertical error of 0.02 m when outliers were removed. Using this new technology, the lidar system has repeatedly flown significant storm events between 2011 and present ( Figure 2B); two of these events that illustrate the different capabilities of the system are described below.…”
Section: Airborne Lidarmentioning
confidence: 96%
“…Aircraft-mounted airborne lidar is a well establish remote sensing tool that is now widely used to obtain high quality topographic data spanning large extents (100 s of kilometers) of coastline [100]. A rapid-response system to fly lidar for storm erosion monitoring was developed jointly by the University of New South Wales' School of Aviation and Water Research Laboratory [101],. The airborne lidar system in use at Narrabeen incorporates a Piper Pa44 Seminole plane equipped with a Riegl Q240i lidar coupled with a NovAtel SPAN-CPT integrated GNSS and IMU.…”
Section: Airborne Lidarmentioning
confidence: 99%
“…As the local stockpiling of sand grains is of the order of a few millimetres, there is a need to distinguish sub-centimetre height variations. Airborne methods only have an accuracy of about one decimetre (Middleton et al 2013). …”
Section: Data Acquisitionmentioning
confidence: 99%